Cryptococcal Meningitis and Post-Infectious Inflammatory Response Syndrome in a Patient With X-Linked Hyper IgM Syndrome: A Case Report and Review of the Literature - Romani, Lorenza; Williamson, Peter Richard; Di Cesare, Silvia; Di Matteo, Gigliola; De Luca, Maia; Carsetti, Rita; Figà-Talamanca, Lorenzo; Cancrini, Caterina; Rossi, Paolo; Finocchi, Andrea (Frontiers in Immunology, 2021)
The hyper IgM syndromes are a rare group of primary immunodeficiency. The X-linked Hyper IgM syndrome (HIGM), due to a gene defect in CD40L, is the commonest variant; it is characterized by an increased susceptibility to a narrow spectrum of opportunistic infection. Few cases of HIGM patients with Cryptococcal meningoencephalitis (CM) have been described in the literature. Herein we report the case of a young male diagnosed in infancy with HIGM who developed CM complicated by a post-infectious inflammatory response syndrome (PIIRS), despite regular immunoglobulin replacement therapy and appropriate antimicrobial prophylaxis. The patient was admitted because of headache and CM was diagnosed through detection of Cryptococcus neoformans on cerebrospinal fluid. Despite the antifungal therapy resulting to negative CSF culture, the patient exhibited persistent headaches and developed diplopia. Analysis of inflammatory cytokines on CSF, as well as the brain MRI suggested a diagnosis of PIIRS. Therefore, a prolonged corticosteroids therapy was started obtaining a complete resolution of symptoms without any relapse.